X-ray structure of LeuT in an inward-facing occluded conformation reveals mechanism of substrate release - Kamil Gotfryd (Nature Communications, 2020)
Neurotransmitter:sodium symporters (NSS) serve as targets for drugs including antidepressants and psychostimulants. Here authors report the X-ray structure of the prokaryotic NSS member, LeuT, in a Na+/substrate-bound, inward-facing occluded conformation which is a key intermediate in the LeuT transport cycle.